A colorimetric multiplex RPA approach for on-site dual monitoring of Vibrio parahaemolyticus and White Spot Syndrome Virus in Pacific Whiteleg shrimp - Tran, Diem Hong; Giang, Vo Ngoc Truc; Phung, Huong Thi Thu; Bui, Le Minh (Vietnam Journal of Biotechnology, 2024)
White spot syndrome virus (WSSV) and Vibrio parahaemolyticus represent the most prevalent and serious pathogens in Viet Nam's shrimp industry, annually inflicting major production losses. With no existing therapeutic measures, timely and accurate diagnosis is imperative for curbing outbreaks and limiting economic impacts through isolation and culling protocols. However, conventional techniques like polymerase chain reaction (PCR) and quantitative PCR require advanced laboratory infrastructure that is incompatible with rapid on-site pathogen surveillance. This work details the development of a multiplex recombinase polymerase amplification (RPA) assay for the simultaneous detection of WSSV and V. parahaemolyticus using a visual colorimetric readout amenable to field deployment. Primers targeting unique WSSV and V. parahaemolyticus sequences were designed for selective amplification. Specificity screening verified exclusive pathogen detection against common shrimp microbiota and human-handling contaminants with no cross-reactivity. Singleplex reactions identified 39 °C for 35 minutes as optimal conditions; hence, these parameters were subsequently applied in multiplex format. Incorporation of the Mg2+-sensitive eriochrome black T (EBT) dye enabled clear discrimination between positive blue and negative violet reactions by the naked eye. The multiplex assay demonstrated high analytical sensitivity, down to 1 copy of DNA template per reaction. Clinical validation of the multiplex RPA method using shrimp samples versus quantitative PCR showed 100% agreement. By coupling rapid isothermal amplification with visual indicator-based detection in a multiplexed format, this assay provides simple, robust, and user-friendly identification of major shrimp pathogens in resource-limited settings in less than one hour to facilitate prompt on-site disease control decisions. The field-suitable platform aims to mitigate outbreak magnitude and economic consequences through timely response.